2016
DOI: 10.1038/sj.bdj.2016.778
|View full text |Cite
|
Sign up to set email alerts
|

A survey of undergraduate orthodontic teaching and factors affecting pursuit of postgraduate training

Abstract: Background Undergraduate orthodontic teaching has been focused on developing an understanding of occlusal development in an effort to equip practitioners to make appropriate referrals for specialist-delivered care. However, there is a growing interest among general dentists in delivering more specialised treatments, including short-term orthodontic alignment. This study aimed to assess the levels of knowledge of occlusal problems among final year undergraduate dental students, as well as their interest in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… 23 Relevant education and training on CAT are therefore critical for good treatment outcomes. 24 Park et al 25 conducted an online survey on CAT education that dental students received from 75 departments in American and Canadian dental schools. The study found that most participants (73.3%) received didactic teaching, whilst 46.7% received clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Relevant education and training on CAT are therefore critical for good treatment outcomes. 24 Park et al 25 conducted an online survey on CAT education that dental students received from 75 departments in American and Canadian dental schools. The study found that most participants (73.3%) received didactic teaching, whilst 46.7% received clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[187,201, At 6.3% came patient education, experience, esthetic and social perception and adjustability, [188,[336][337][338][339][340][341][342][343][344][345][346] as well as miscellaneous considerations including factors influencing career choice, future aspirations, use of CA by orthodontists and general practitioners, the impact of digital scanning on CA popularity and the documentation of the most highly cited articles. [347][348][349][350][351][352][353][354][355][356][357][358] Geometrical considerations associated with CAT, representing 5.8% of the studies, primarily explored attachment configurations clinically, the efficiency of power ridges, retention, and fit of CA with various attachments and incidence of attachments loss. [200,312,[359][360][361][362][363][364][365][366][367][368] e final place was occupied by biomechanical considerations accounting for only 4% of the published outcome domains.…”
Section: Discussionmentioning
confidence: 99%
“…Explore the criteria used by graduate students while selecting a career as orthodontists and their future aspirations G Jauhar et al, 2016 [351] Cross-sectional survey [352] Interrupted time series Cross-sectional analysis 1,871 GP and orthodontic practices worldwide 319 low-volume, North American GPs Impact of digital scanning in GDPs and orthodontic practices to determine the percent increase in gross receipts of Invisalign ® treatment • 48 months (24 pre-and 24 post-scanner introduction) of Invisalign receipt…”
Section: Motivations and Future Practice Plans Of Orthodontic Residen...mentioning
confidence: 99%
“…Universities may have to change the curriculum for students or professionals to meet future market demands. In a UK survey, 59% of undergraduate students showed interest in Invisalign courses [ 40 ]. An earlier study suggested that patients are willing to pay more for orthodontic services provided by doctors with higher levels of formal education.…”
Section: Discussionmentioning
confidence: 99%